What is the best titration protocol for dimethyl fumarate? Preliminary results of a multicenter real-world study - Yetkin, M.; Duman, T.; Bilge, N.; Gokce, S.; Ethemoglu, O.; Akcali, A.; Altun, Y. (Wiley, 2023)
[Abstract Not Available]